Early inhalant allergen sensitization at component level: an analysis in atopic Dutch children - Landzaat, Lonneke J.; Emons, Joyce A. M.; Sonneveld, Laura J. H.; Schreurs, Marco W. J.; Arends, Nicolette J. T. (Frontiers in Allergy, 2023)
Background – Allergic rhinitis is a common respiratory disease in children and sensitization to inhalant allergens plays a significant role in its development. However, limited knowledge exists regarding sensitization profiles of inhalant allergen components in atopic children, particularly in very young individuals. Understanding these profiles could provide insights into early development of allergic rhinitis. The objective of this study was to evaluate IgE-sensitization profiles to multiple inhalant allergen components and their clinical relevance in Dutch atopic children, with specific focus on children under 4 years of age. Methods – 243 atopic children were included in the study and sensitization profiles were analyzed using multiplex microarray analysis (ISAC). Clinical information was obtained between 2011 and 2020. Specific IgE responses to inhalation allergen components from five allergen sources (grass pollen, tree pollen, house dust mite, cat and dog), were examined. The study encompassed children of different age groups and compared those with and without symptoms. Results – The results demonstrated that sensitization to inhalant allergen components was present in 92% of the cohort. Sensitization was already evident at a young age (87%), including infancy, with a rapid increase in prevalence after 1 year of age. House dust mite emerged as most predominant sensitizing allergen in early childhood, followed by tree pollen in later years. Sensitization patterns were similar between symptomatic and asymptomatic children, although symptomatic children exhibited higher frequencies and values. Sensitization profiles in very young children were comparable to those of children across all age groups. Conclusion – These findings highlight the presence of sensitization to inhalant allergen components and the early onset of allergic rhinitis before the age of 4, including infancy, in Dutch atopic children. Notable allergen molecules in Dutch young atopic children include Bet v 1, Fel d 1, Der f 1, Der p 1, Der p 10 and Phl p 4, with house dust mite sensitization being most common among Dutch infants. Moreover, the prevalence of sensitization to inhalant allergens in this Dutch cohort surpassed that of general European populations, emphasizing the importance of early assessment and management of allergic rhinitis in young atopic children.